2000
DOI: 10.1002/(sici)1099-1379(200002)21:1<25::aid-job2>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Re-examining the effects of psychological contract violations: unmet expectations and job dissatisfaction as mediators

Abstract: This research examines whether the relationships between psychological contract violations and three types of employee behavior (intention to quit, neglect of in-role job duties, and organizational citizenship behaviors) are mediated by unmet expectations and job dissatisfaction. Using a sample of over 800 managers from a wide variety of research sites, this study tests for mediator e€ects using both hierarchical regression analyses and structural equation modelling. The results suggest that unmet expectations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
403
3
34

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 550 publications
(468 citation statements)
references
References 27 publications
28
403
3
34
Order By: Relevance
“…In contrast, relational obligations are more open-ended, intrinsic, dynamic and subjective (e.g., job security) (Conway and Briner 2009;Rousseau and McLean Parks 1993). PC therefore covers a range of issues like trust, fairness, promotion, training, development and decision making (Conway and Briner 2005;Turnley and Feldman 2000). Studies of work-related stress have argued that breaches and violations of PC can make a significant contribution to the stress experienced by employees (Noblet et al 2009).…”
mentioning
confidence: 99%
“…In contrast, relational obligations are more open-ended, intrinsic, dynamic and subjective (e.g., job security) (Conway and Briner 2009;Rousseau and McLean Parks 1993). PC therefore covers a range of issues like trust, fairness, promotion, training, development and decision making (Conway and Briner 2005;Turnley and Feldman 2000). Studies of work-related stress have argued that breaches and violations of PC can make a significant contribution to the stress experienced by employees (Noblet et al 2009).…”
mentioning
confidence: 99%
“…Most applicable to the current study, Turnley and Feldman used a dimensional measure of the degree of psychological contract violations rather than a global measure. 18 Their measure of contract violation incorporates multiple items addressing 16 different aspects of the employment relationship. Furthermore, the measure allows respondents to indicate whether each aspect of their contract was unfulfilled, fulfilled, or over fulfilled.…”
Section: Measuring Psychological Contract Violationsmentioning
confidence: 99%
“…15,18 The 16-item measure developed by Turnley and Feldman 18 assesses aspects of the employment relationship that represent potential organizational obligations within the psychological contract as identified by previous research. 7,15,20 Those aspects include: pay, work content, opportunity for advancement, benefits, job security, training, development, feedback, and organizational and supervisory support.…”
Section: Initial Measure Developmentmentioning
confidence: 99%
“…In their seminal paper, Robinson and Rousseau (1994) showed that PCB is more the norm than the exception, and, when it happens, can lead to undermined trust between employee and employer, dissatisfaction among employees and even the dissolution of the relationship. Consistent with that, it has been shown that that PCB is negatively related to job satisfaction (Raja, Johns & Ntalianis, 2004), intention to stay in the organization (Turnley & Feldman, 2000), job performance (Johnson & O'Leary-Kelly, 2003), trust in the organization (Zhao et al, 2007), organizational citizen behaviors (Restubog, Bordia & Tang, 2007) and organizational commitment (Zhao et al, 2007). At the same time, PCB was shown to be positively correlated with counterproductive work behaviors (Bordia, Restubog & Tang, 2008), absenteeism and organizational cynicisms (Johnson & O'Leary-Kelly, 2003).…”
Section: Introductionmentioning
confidence: 99%